Compact 3D monolithic microwave integrated circuit bandpass filter based on meander resonator for 5G millimeter-wave - Sinulingga, Emerson Pascawira; Nasution, Abdul Risyal (International Journal of Electrical and Computer Engineering (IJECE), 2024)
Bandpass filters for millimeter-wave band applications are typically designed using resonators. However, the design of a multilayer coplanar waveguide (CPW) monolithic microwave integrated circuit (MMIC) bandpass filter for 5G millimeter-wave band, n257 with operating frequencies from 26.5 to 29.5 GHz is still not available. Therefore, in this work, a compact bandpass filter for 5G millimeter-wave application was designed with multilayer CPW MMIC bandpass filter based on a meander resonator. The meander resonator of the bandpass filter was designed using low-loss multilayer CPW lines. In designing the bandpass filter, the resonator length and perturbation was utilized to optimize the resonance and bandwidth, and meander resonator was used to miniaturize the bandpass filter. As result, a compact bandpass filter with size of 0.75×0.75 mm2 for 5G millimeter-wave band n257 was achieved. It has bandwidth of 3 GHz, an insertion loss of -2.87 dB and a return loss of -11.1 dB at frequency 28 GHz.